2D platform-based game of arithmetic game-based learning - Zoe, Yee Tze Yun; Wahid, Noorhaniza; Murli, Norhanifah; A Hamid, Rahayu; Othman, Muhammad Fakri (IOP Publishing, 2018)
Mobile games have attracted attention among game developers and users. Throughout the years, mobile games have developed to become one of the domination of the digital world. They have evolved from just a non-coloured with few animated dots and lines to a coloured and more realistic three-dimensional gameplay. Besides, mobile games do not only act as an entertainment but also as a medium for improving mental arithmetic skill if the content is designed accordingly. However, most of mobile games nowadays have been developed for leisure purpose only. There is less game on IQ test and education while more on skills and action alternatively. Hence, arithmetic game-based learning application is developed as an alternative to be included in the variety of gameplay or content of the game. The game created based on platform genre with endless running style. Arithmetic questions are provided in the gameplay as one of the obstacles to both provide challenges and IQ test for the players. This game is implemented in mobile platform. Technology Acceptance Model (TAM) is adopted to measure the game quality based on the evaluation of user acceptance level towards the gameplay, functionality and playability, and overall performance of the game. Overall, 50% of respondents agreed that the gameplay is satisfying. In addition, 40% of respondents strongly agreed that the functionality and playability of the game is stable and the overall performance of the game functions perfectly.